Menstrual Knowledge Status among School Going Girls in Mulundi Sub-Location, Kitui County - Mercy Mukai Kalio; Felix Kioli Ngunzo; Kennedy Barasa Wanjala (Journal of Sociological Research, 2024)
Menstruation is part of female human health that signifies the transition from childhood to adulthood. Correct menstrual knowledge entails having accurate knowledge of physiological changes, which accompanies body changes. Knowledge extends to being well versed with the advantages of correct menstrual practices and the consequences of poor menstrual management. Menstrual hygiene knowledge was evaluated in four (4) primary and 3 secondary schools within Mulundi sub Location. Mulundi sub Location was chosen among many areas due to its economic status, which is similar to that of most sub-Locations within Kitui County. The sampled schools draw their learner’s population within the location and the immediate locations thus a good representation of the area. The study adopted a mixed-method approach, which involved the collection of qualitative and quantitative data. Quantitative data was collected using questionnaires administered to 140-school going girls aged between 10-19 years. The qualitative data was acquired through the use of focused group discussions and key informant interviews. The qualitative data reported as verbatim quotes suggest more campaigns are needed to enlighten girls on the menstrual subject. The study reveals that 68% of the girls could define menstruation correctly while 14% and 9% thought it was a disease and curse respectively. A percentage constituting 9% had no idea of menstruation. The parents were ranked as the highest source of menstrual information constituting a percentage of 39.1%. Based on the study findings, teachers contributed 33.2% of the menstrual knowledge by girls. Other sources of menstrual knowledge included individuals, peer educators and religious groups. Though over half of the sampled population were knowledgeable, the study recommends the inclusion of more sessions on the menstrual subject in the school’s curriculum.